Réordonner l’espace et le temps : - Nicolas Senil (Revue de Géographie Alpine)
The multiplication of objects, actors and underlying rationales of heritage development, or patrimonialisation, is increasingly blurring the strength and meaning of our relationship with the past. The aim of this article is to reflect on the processes involved in the emergence of new heritage objects and on the consequences of these developments. The article is based on a comparative analysis of two symmetric objects, both of which have been the subject of heritage development processes: the Chauvet cave and the Millau viaduct in Southern France. By showing that each object is projected in the spatial or temporal dimension from which it was a priori excluded at the time of its discovery, the analysis demonstrates the necessity of integrating a heritage approach to our understanding of territorial dynamics. The analysis suggests that the interplay of territorialisation and heritage development processes represents a reconstruction of a controlled time-space, a prerequisite for addressing a recurring problem in our society, that of its sustainability.